2015
DOI: 10.7567/jjap.55.01ab05
|View full text |Cite
|
Sign up to set email alerts
|

Plasma polymerization of acrylic acid onto polystyrene by cyclonic plasma at atmospheric pressure

Abstract: The cyclonic atmospheric-pressure plasma is developed for chamberless deposition of poly(acrylic acid) film from argon/acrylic acid mixtures. The photoemission plasma species in atmospheric-pressure plasma polymerization was identified by optical emission spectroscopy (OES). The OES diagnosis data and deposition results indicated that in glow discharge, the CH and C2 species resulted from low-energy electron-impact dissociation that creates deposition species, but the strong CO emission lines are related to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…The Yasuda parameter has been applied to atmospheric pressure systems with mixed applicability . Morent et al reported the effects of W / FM on deposition rate of a dielectric‐barrier discharge (DBD) for PECVD of HMDSO and described a decrease in deposition rate at a higher region of the monomer‐deficient domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Yasuda parameter has been applied to atmospheric pressure systems with mixed applicability . Morent et al reported the effects of W / FM on deposition rate of a dielectric‐barrier discharge (DBD) for PECVD of HMDSO and described a decrease in deposition rate at a higher region of the monomer‐deficient domain.…”
Section: Introductionmentioning
confidence: 99%
“…Deposition rate, however, was not evaluated using the normalized parameter, GR / FM , and it is unclear if the values would be similar, perhaps if also using the porosity to calculate an equivalent thickness and dividing by monomer flow rate. Chang et al used a cyclonic plasma at atmospheric pressure to polymerize acrylic acid under various power and flow rates. Surface energy did not follow a trend with W / FM , while power independently showed a significant effect.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the polar and dispersive components, the tendency of the polar component is similar to that of the surface energy, but the dispersive component remains at a constant value. The constant values of the dispersive component indicate that the variation in surface roughness is scarcely appreciable . The chemical structure and the bonding modes of cyclonic atmospheric pressure HMDSN and HMDSN/N 2 plasma deposited SS316 samples were evaluated by ATR‐FTIR.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of obtained results with values reported in literature allows to recognise similar trends although variations rise from different plasma polymerization conditions and coated substrates. Thus, Jafari et al [89] reported a variation from 90 • for a non-treated PE film to an average of less than 10 • , for an unwashed PPAA coating; Chang et al [94] reported a spectra of water contact angles ranging from 5 to 30 • of atmospheric-pressure plasma pp-AAc thin films on PS (92 • ) depending on the plasma polymerization conditions. Further, the increased wettability of inorganic substrates has been similarly reported by Ward et al [95] for glass slides (WCA <15 • C) and by Vilani et al [50] who reduced the WCA of untreated Si (100) from 65 • to 30-55 • WCA using PAA under several plasma power conditions.…”
Section: Resultsmentioning
confidence: 99%